Regioselective convergent synthesis of 2-arylidene thiazolo[3,2-: A] pyrimidines as potential anti-chikungunya agents - Fares, Mohamed; McCosker, Patrick M.; Alsherbiny, Muhammad A.; Willis, Anthony C.; Clark, Timothy; Neyts, Johan; Jochmans, Dirk; Keller, Paul A. (RSC Advances, 2020)
Convergent and convenient regioselective synthesis of novel thiazolo[2,3-a]pyrimidine derivatives was accomplished using the one-pot reaction of 6-ethylthiouracil, bromoacetic acid, anhydrous sodium acetate, acetic anhydride, acetic acid and suitable aldehyde. X-ray crystallographic study reveals the presence of the Z configuration of only one regioisomer confirmed by computational studies as being the most likely isomer present.
CRIS-Team Scopus Importer:2020-02-21